Espectroeletroquímica e calibração de segunda ordem no desenvolvimento de métodos analíticos - Oliveira, Levi Gomes de (2022)
This work aims to demonstrate the possibility of using spectroelectrochemistry in the acquisition of second-order data, and to evaluate pre-processing and treatment strategies applied to these data. Two experimental setups were used in the acquisition of experimental data. The first experimental setup combines molecular absorption spectroscopy and voltammetric techniques. The second setup combines reflectance spectroscopy with linear scanning voltammetry. Potassium ferrocyanide and o-tolidine were used as model systems in the validation of the first and second experimental setups, respectively. After verifying the experimental setups, two applications were proposed. As a first application, the spectroelectrochemistry of the benzenediol isomers hydroquinone, catechol and resorcinol was studied through the first experimental setup. Two calibration strategies were used to model the data obtained through the first experimental setup. In the first strategy, untreated data were used for calibration. RMSEPs of 0.03, 0.06 and 0.07 mmolL−1 were obtained through PARAFAC models for hydroquinone, catechol and resorcinol, respectively. For the U-PLS/RBL models, RMSEPs of 0.03, 0.05 and 0.10 mmolL−1 were obtained for hydroquinone, catechol and resorcinol, respectively. In the second strategy, data pre-processed by calculating the first derivative in relation to the potential were used. RMSEPs of 0.05 and 0.06 mmolL−1 were obtained through PARAFAC models for hydroquinone and catechol, respectively. For the U-PLS/RBL models, RMSEPs of 0.07, 0.07 and 0.04 mmolL−1 were obtained for hydroquinone, catechol and resorcinol, respectively. As a second application, the spectroelectrochemistry of dopamine and epinephrine was studied through the second experimental setup. Data from this system were modeled using PARAFAC. Predictions with test samples resulted in RMSEPs of 0.04 and 0.05 mmolL−1 for dopamine and epinephrine, respectively. In studies on the spectroelectrochemistry of benzenediol isomers, degenerate solutions were found in PARAFAC models. A theoretical study was conducted to investigate the effects of degeneracy. It was found that degeneracy is associated with the fact that an analyte can be present in at least two forms, whose total concentration is constant. Degeneracy ends up being related to the uniqueness of solutions and adequate determination of the number of factors in the model. The theoretical study showed some possible effects of the degeneracy of solutions in the qualitative results and the role of restrictions in the modeling.